Menelusuri Akar Masalah: Faktor-Faktor Penyebab Kesehatan Mental pada Remaja Indonesia - Ika Putri Rahmayani; M. Suharsono (EduInovasi: Journal of Basic Educational Studies, 2025)
This study explores the factors influencing the mental health of adolescents in Indonesia, focusing on social, familial, and environmental aspects. Through a literature analysis, it was found that strong family support, positive parenting styles, and good interpersonal relationships play a crucial role in adolescent mental health. Additionally, the impact of social media and environmental conditions were identified as significant factors that can worsen mental health if not managed properly. The findings suggest that enhancing emotional support from families, educating about healthy social media use, and providing more accessible mental health services are essential. This study also identifies gaps in existing research, recommending further studies to understand the interaction between these factors in diverse contexts across Indonesia. By implementing the proposed recommendations, it is hoped that a healthier and more resilient generation of adolescents can be fostered.